Tuberkuloma : Sebuah Laporan Kasus - Fitriyani, Fitriyani; Suwanda, Meyliana; Perdana, Aditya Andra; Mellisa, Stefani (Medula, 2023)
Intracranial tuberculoma is a rare but severe form of extrapulmonary tuberculosis with high mortality and morbidity rates. Early diagnosis and treatment are crucial determinants of tuberculoma prognosis. A 61-year-old female presented to the emergency department of RSAM with complaints of headache, nausea, and vomiting for the past 2 months prior to hospital admission. The patient had a history of weight loss for 5 months before hospitalization, a history of dry cough, and night sweats for the last 2 months before admission. Radiological examination via a head MRI revealed multiple lesions, with the largest measuring 1.7x1.3x1.8 cm in the left parietal cortical lobe and the right frontal lobe, suspected to be tuberculomas. A CT scan of the thorax showed multiple consolidations in the lateral segment of the right lower lobe with a long axis of 1.1 cm and in the anterior segment of the left lower lobe with a long axis of 1.6 cm, suspected of malignancy with concomitant active long-standing pulmonary tuberculosis and endobronchial spreading. The patient was treated with anti-tuberculosis drugs and corticosteroids. She was discharged with reduced headache and vomiting. The rare occurrence and atypical clinical manifestations, along with radiological characteristics, pose challenges in diagnosing tuberculomas. Establishing a diagnosis and initiating treatment as early as possible is crucial and key to the prognosis of tuberculomas.